Hubungan Pengetahuan dan Pendidikan Ibu terhadap Status Gizi Balita - Numaliza, Numaliza; Herlina, Sara (KESMARS: Jurnal Kesehatan Masyarakat, Manajemen dan Administrasi Rumah Sakit, 2018)
Nutritional status is the state of the body as a result of eating foods and the use of nutrients.Society Nutrition Status is one of the Indonesia health issues. One of indicator of Society Nutritional Status is the toddler nutritional status. Efforts to achieve the good toddler nutritional status is knowledge of parents, especially mothers as caregivers and her responsibility in family meals implementation including for children. Therefore mothers understanding of toddler food and nutrition is very important. The purpose of this research to determine the relationship of knowledge and education to the nutritional status of children. This research is a quantitative analytic research with cross sectional approach. Sample in this research is some mothers who have toddler counted 70 people. The sampling technique used was purposive sampling. This study was analyzed univariat and bivariate. The result of the research is based on chi square test with Pvalue value less than 0,05 (less than 0,006 <0,05) and (less than 0,034 less than 0,05). The conclusion of this research is there is relationship between knowledge and education to the Toddler nutritional status Keywords : Nutritional Status, Toddler, Education , knowledge